Patch Formulation from the Extract of Banana Leaf Sheath (Musa paradisiaca L.) and Kersen Leaf (Muntingia calabura L.) with HPMC Polymer - Udianto, Abi Mas; Artemisia, Stephanie Devi; Prasasti, Azmi; Prayudeni, Sari; Fayzannaja, Safina (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Indonesia possesses rich biodiversity with strong potential as a source of raw materials for traditional medicine. Both banana stalks (Musa paradisiaca L.) and kersen leaves (Muntingia calabura L.) contain secondary metabolites, such as flavonoids, tannins, and saponins, which are associated with wound-healing properties. This study aims to formulate and evaluate the physical characteristics of a transdermal patch containing a combination of banana stem and kersen leaf extracts using Hydroxypropyl Methylcellulose (HPMC) polymer. The study was conducted as a laboratory experiment. Extraction was performed using the maceration method with 96% ethanol, after which the extracts were formulated into patches with HPMC concentrations of 2.5%, 5%, and 7.5%. Extracted with 96% ethanol, after which the extracts were formulated into patches using varying HPMC concentrations of 2.5%, 5%, and 7.5% with a fixed extract concentration. The results indicated that different HPMC concentrations significantly affected the physical characteristics of the patches, such as thickness, folding endurance, and appearance. Physical evaluation included organoleptic testing, weight uniformity, thickness, fold resistance, pH, and freeze-thaw stability. The results showed that all formulations met the physical quality requirements, with a standard deviation for weight uniformity of ≤0.05, thickness of ≤1 mm, fold resistance of >300 times, a pH of 6, and good physical stability. Variations in extract concentration affected the color of the plaster, with higher extract concentrations resulting in darker colors. Based on the evaluation results, the plaster made from banana leaf sheathand kersen leaf extracts combined with HPMC polymer meets the requirements for a high-quality plaster formulation. Variations in extract concentration affected the color of the patch, with higher extract concentrations resulting in darker coloration. Based on the evaluation results, the patch formulas combining banana stem and kersen leaf extracts with HPMC polymer met the standard physical requirements for an acceptable topical patch formulation.